Network Neutrality in Peru: A Retrospective - Morachimo Rodríguez, Miguel (2017)
This paper documents the evolution of the Network Neutrality Principle regulation in Peruvian Law during the last decade, through a detailed study of the several laws that have built it. Since their almost accidental beginnings to the recently published Regulation by OSIPTEL in 2016, this work highlights the lack of a clear and consistent regulatory objective behind these efforts.